Evaluation of the Impact of the Online Game Mobile Legends on Users’ Mental Health using the Fuzzy Logic Method - Kurniawansyah, Fito Cahya; Munzir, Medyantiwi Rahmawita; Mustakim, Mustakim; M. Afdal, M. Afdal; Marsal, Arif (Sistemasi: Jurnal Sistem Informasi, 2025)
One of the benefits of advancing technology is its ability to serve as a medium for entertainment. The online game Mobile Legends has gained widespread popularity and attracts a broad audience, including university students. While playing Mobile Legends can offer cognitive stimulation, enjoyment, and entertainment, it can also lead to excessive addiction, which may negatively affect users’ mental health. This study applies a fuzzy logic approach, which processes input data through fuzzy rules involving fuzzification, fuzzy inference, and defuzzification. Three input variables are used: Playing Time, Emotional Level, and Stress Level, with a single output variable: Health Index, which reflects the user's mental health condition. The purpose of this study is to evaluate the impact of the Mobile Legends online game on users’ mental health using fuzzy logic implemented in MATLAB. Based on the results, the manual Mamdani fuzzy analysis yielded a defuzzification result of 44.75. Meanwhile, using MATLAB Fuzzy Mamdani Toolbox (version 2023b) with input values of Playing Time (69), Emotional Level (68), and Stress Level (65) produced an output of 52.7. Both results fall within the fuzzy domain of “Agree” [40, 60, 80], indicating that prolonged playing time of Mobile Legends can influence players’ mental health.